2022
DOI: 10.1097/gox.0000000000004634
|View full text |Cite
|
Sign up to set email alerts
|

Office-based Plastic Surgery—Evidence-based Clinical and Administrative Guidelines

Abstract: Summary: Outpatient procedures are extremely prevalent in plastic surgery, with an estimated 82% of cosmetic plastic surgery occurring in this setting. Given that patient safety is paramount, this practical review summarizes major contemporary, evidence-based recommendations regarding office-based plastic surgery. These recommendations not only outline clinical aspects of patient safety guidelines, but administrative, as well, which in combination will provide the reader/practice with a structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 106 publications
(305 reference statements)
0
5
0
2
Order By: Relevance
“…Aesthetic surgeries have transitioned from occurring primarily in hospital settings to being almost exclusively outpatient, with approximately 82% of procedures taking place in the ambulatory setting in 2020. 11 Oppositely, the majority of research surrounding cosmetic surgery has been based on inpatient data. Therefore, this analysis of liposuction complications from procedures performed in outpatient QUAD A–certified facilities aims to open a window into the ambulatory surgery space on a national level.…”
Section: Discussionmentioning
confidence: 99%
“…Aesthetic surgeries have transitioned from occurring primarily in hospital settings to being almost exclusively outpatient, with approximately 82% of procedures taking place in the ambulatory setting in 2020. 11 Oppositely, the majority of research surrounding cosmetic surgery has been based on inpatient data. Therefore, this analysis of liposuction complications from procedures performed in outpatient QUAD A–certified facilities aims to open a window into the ambulatory surgery space on a national level.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 1 state that plastic surgeons must assess venous thromboembolism (VTE) risk by recording predisposing conditions and lifestyle factors. Interestingly, Pannucci et al 2 recently reported that 80% of women who develop VTE after breast augmentation are likely to have Caprini scores less than or equal to 6.…”
Section: Sirmentioning
confidence: 99%
“…The authors agree with the consensus panel of the American Association of Plastic Surgeons 4 in stating, “there is no all-encompassing recommendation regarding VTE chemoprophylaxis based on Caprini stratification and surgeons should use clinical judgment when evaluating patients for VTE management.” 1 However, the authors go on to say that abdominoplasty is an exception and that studies have shown a benefit in using VTE chemoprophylaxis in abdominoplasty patients. Four references are cited.…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative core body temperature is a surgical factor that has been previously associated with thrombotic events after surgical procedures such as ovarian cytoreductive surgery, intracranial tumor resection, and various forms of microsurgical free tissue transfer. [7][8][9][10][11][12] Although investigations from the basic science literature have suggested that mild hypothermia might protect against thrombosis due to inhibition of platelet function and the clotting cascade, results from these studies have been discordant with clinical studies. [13][14][15] Thus, the question arises whether intraoperative core body temperature may be a predictive factor of VTE after CAWR.…”
Section: Introductionmentioning
confidence: 99%